Child Maltreatment and Executive Functioning in Middle Adulthood: A Prospective Examination - Nikulina, Valentina (2013)
OBJECTIVE: There is extensive evidence of negative consequences of childhood maltreatment for IQ, academic achievement, and post-traumatic stress disorder (PTSD) and increased attention to neurobiological consequences. However, few prospective studies have assessed the long-term effects of abuse and neglect on executive functioning. The current study examines whether childhood abuse and neglect predicts components of executive functioning and nonverbal reasoning ability in middle adulthood and whether PTSD moderates this relationship. METHOD: Using a prospective cohort design, a large sample (N = 792) of court-substantiated cases of childhood physical and sexual abuse and neglect (ages 0-11) and matched controls were followed into adulthood (mean age = 41). Executive functioning was assessed with the Trail Making B test and non-verbal reasoning with Matrix Reasoning. PTSD (DSM-III-R lifetime diagnosis) was assessed at age 29. Data were analyzed using ordinary least squares regressions, controlling for age, sex, and race and possible confounds of IQ, depression, and excessive alcohol use. RESULTS: In multivariate analyses, childhood maltreatment overall and childhood neglect predicted poorer executive functioning and non-verbal reasoning at age 41, whereas physical and sexual abuse did not. A past history of PTSD did not mediate or moderate these relations. CONCLUSIONS: Childhood maltreatment and neglect specifically have a significant long-term impact on important aspects of adult neuropsychological functioning. These findings suggest the need for targeted efforts dedicated to interventions for neglected children.